High flex cycle testing of CVD monolayer WS2 TFTs on thin flexible polyimide. (9th May 2016) - Gong, Yiyang; Carozo, Victor; Li, Haoyu; Terrones, Mauricio; Jackson, Thomas N
Abstract: Two-dimensional transition metal dichalcogenides are potential candidates for high-performance flexible electronics. In this paper, we report thin film transistors (TFTs) fabricated on ∼5 μ m thick solution-cast polyimide substrates using chemical vapor deposition (CVD) synthesized single layer WS2 as the active layer. The linear region field effect mobility ranges from 2 to 10 cm 2 V −1 s −1, with current on–off ratio exceeding 10 6 . By using a thin polyimide substrate, the bending induced tensile stress on our TFTs is relatively small when compared to devices fabricated on thicker flexible substrates. Static bending and up to 50 000 bending/flattening cycles were employed to investigate the reliability of these TFTs for potential flexible electronic applications. Our results demonstrate that CVD grown WS2 TFTs fabricated on thin polyimide have good performance stability for up to 2 mm radius bending and 50 000 bending cycles. It is therefore clear that thin polymeric substrates provide a simple approach for reliable, scalable, and high-performance 2D-TMD-based flexible electronics.